EXPLORING BANGGAI COASTAL CULTURE LITERATURE AS ENGLISH READING MATERIALS TO INCREASE STUDENTS’ CULTURAL AWARENESS - Nurafni Azzahra Dg Pacidda; Mifta Zalianti; Kasih Marchela Z. Larau; Anitha Thalib Mbau; Nadya Septiani Rahman; Nurlaela (e-Journal of ELTS (English Language Teaching Society), 2026)
This study aims to identify what local literature of Banggai coastal culture is appropriate as English reading materials for junior high school students to enhance their cultural awareness. This study employs content analysis. The data sources are two books about Banggai folktales written in English. The data are collected by applying note-taking techniques. The instruments used to gather the data include the researchers as the primary data collectors and analysts, a rubric of analytical constructs as a guide for collecting relevant data, and datasheets as the media for recording the data. The data, then, are analyzed both quantitatively and qualitatively. Inter-coder agreement (peer debriefing) is used to maintain the trustworthiness of the study. This study finds that Banggai folktales are predominantly characterized by cultural aspects, including behaviors (35%) and norms (31%). However, readability analysis reveals that more than half of the twenty-seven texts fell into the uneven (55.5%) and invalid (26%) categories, and only a few texts, such as "The Legend of Lemelu Lake" and "The Legend of Tendetung Lake," are at an appropriate level for grade 7. This study is limited to text analysis without classroom application. The study concludes that Banggai folktales hold promise as alternative EFL reading materials, given that teachers adapt the texts to balance cultural richness with readability.